Development of dabai nutcracker - Mohamad Ghazali, Aida Nabila; Shamsudin, Rosnah; Jalil, Muhammad Siddiq Amir (Malaysian Society of Agricultural Engineers, 2019)
Dabai fruit is one of the underutilized fruit originated from Sarawak which rich with nutritional values. The flesh can be eaten raw after soaking it in warm water. The nuts from the seeds can also be consumed as it tastes like peanuts. There are also recent findings indicates that the nutritional quality of Dabai oil or canarium oil is most likely to be similar to the composition of palm oil such as the palmitic acid, linoleic acid, and linolenic acid. Dabai nutcracker is designed to separate the kernel from the nut. The design is to help in solving the difficulties in cracking the nuts of Dabai fruits, difficulties in accessing the whole kernel when using ready stock nutcracker because the uniqueness of the shape and the shell is very hard to rupture. The main objective of this research is to design, develop and evaluate the performance of the device. The dimension of the tool is 351 mm (upper part length) x 250 mm (bottom part length) x 144.09 mm (height) x 100 mm (width). The performance capacity of this tool is 1.64 kg/hr and gives 97.27 % in overall efficiency.